76.25.16 problem 20
Internal
problem
ID
[17829]
Book
:
Differential
equations.
An
introduction
to
modern
methods
and
applications.
James
Brannan,
William
E.
Boyce.
Third
edition.
Wiley
2015
Section
:
Chapter
6.
Systems
of
First
Order
Linear
Equations.
Section
6.3
(Homogeneous
Linear
Systems
with
Constant
Coefficients).
Problems
at
page
408
Problem
number
:
20
Date
solved
:
Tuesday, January 28, 2025 at 11:03:32 AM
CAS
classification
:
system_of_ODEs
\begin{align*} \frac {d}{d t}x_{1} \left (t \right )&=x_{1} \left (t \right )+8 x_{2} \left (t \right )+5 x_{3} \left (t \right )+3 x_{4} \left (t \right )\\ \frac {d}{d t}x_{2} \left (t \right )&=2 x_{1} \left (t \right )+16 x_{2} \left (t \right )+10 x_{3} \left (t \right )+6 x_{4} \left (t \right )\\ \frac {d}{d t}x_{3} \left (t \right )&=5 x_{1} \left (t \right )-14 x_{2} \left (t \right )-11 x_{3} \left (t \right )-3 x_{4} \left (t \right )\\ \frac {d}{d t}x_{4} \left (t \right )&=-x_{1} \left (t \right )-8 x_{2} \left (t \right )-5 x_{3} \left (t \right )-3 x_{4} \left (t \right ) \end{align*}
✓ Solution by Maple
Time used: 0.139 (sec). Leaf size: 88
dsolve([diff(x__1(t),t)=1*x__1(t)+8*x__2(t)+5*x__3(t)+3*x__4(t),diff(x__2(t),t)=2*x__1(t)+16*x__2(t)+10*x__3(t)+6*x__4(t),diff(x__3(t),t)=5*x__1(t)-14*x__2(t)-11*x__3(t)-3*x__4(t),diff(x__4(t),t)=-1*x__1(t)-8*x__2(t)-5*x__3(t)-3*x__4(t)],singsol=all)
\begin{align*}
x_{1} \left (t \right ) &= c_{2} +c_{3} {\mathrm e}^{9 t}+c_4 \,{\mathrm e}^{-6 t} \\
x_{2} \left (t \right ) &= 2 c_{2} +2 c_{3} {\mathrm e}^{9 t}+2 c_4 \,{\mathrm e}^{-6 t}+c_{1} \\
x_{3} \left (t \right ) &= -c_{3} {\mathrm e}^{9 t}-4 c_4 \,{\mathrm e}^{-6 t}-c_{2} -c_{1} \\
x_{4} \left (t \right ) &= -c_{3} {\mathrm e}^{9 t}-c_4 \,{\mathrm e}^{-6 t}-4 c_{2} -c_{1} \\
\end{align*}
✓ Solution by Mathematica
Time used: 0.011 (sec). Leaf size: 311
DSolve[{D[x1[t],t]==1*x1[t]+8*x2[t]+5*x3[t]+3*x4[t],D[x2[t],t]==2*x1[t]+16*x2[t]+10*x3[t]+6*x4[t],D[x3[t],t]==5*x1[t]-14*x2[t]-11*x3[t]-3*x4[t],D[x4[t],t]==-1*x1[t]-8*x2[t]-5*x3[t]-3*x4[t]},{x1[t],x2[t],x3[t],x4[t]},t,IncludeSingularSolutions -> True]
\begin{align*}
\text {x1}(t)\to \frac {1}{3} e^{-6 t} \left (c_1 \left (e^{6 t}+e^{15 t}+1\right )+c_2 \left (-e^{6 t}+2 e^{15 t}-1\right )+c_3 e^{15 t}-c_4 e^{6 t}+c_4 e^{15 t}-c_3\right ) \\
\text {x2}(t)\to \frac {1}{3} e^{-6 t} \left (2 c_1 \left (-2 e^{6 t}+e^{15 t}+1\right )+c_2 \left (e^{6 t}+4 e^{15 t}-2\right )+2 c_3 e^{15 t}-2 c_4 e^{6 t}+2 c_4 e^{15 t}-2 c_3\right ) \\
\text {x3}(t)\to \frac {1}{3} e^{-6 t} \left (-\left (c_1 \left (-5 e^{6 t}+e^{15 t}+4\right )\right )-2 c_2 \left (e^{6 t}+e^{15 t}-2\right )-c_3 e^{15 t}+c_4 e^{6 t}-c_4 e^{15 t}+4 c_3\right ) \\
\text {x4}(t)\to \frac {1}{3} e^{-6 t} \left (-\left (c_1 \left (-2 e^{6 t}+e^{15 t}+1\right )\right )+c_2 \left (e^{6 t}-2 e^{15 t}+1\right )-c_3 e^{15 t}+4 c_4 e^{6 t}-c_4 e^{15 t}+c_3\right ) \\
\end{align*}